Agents and artificial intelligence : 10th International Conference, ICAART 2018, Funchal, Madeira, Portugal, January 16-18, 2018, Revised selected papers /: 10th International Conference, ICAART 2018, Funchal, Madeira, Portugal, January 16-18, 2018, Revised selected papers. (2019) - Unknown
No abstract available